A Review of Hot-Melt Extrusion: Process Technology to Pharmaceutical Products. (27th December 2012) - Maniruzzaman, Mohammed; Boateng, Joshua S.; Snowden, Martin J.; Douroumis, Dennis
Abstract : Over the last three decades industrial adaptability has allowed hot-melt extrusion (HME) to gain wide acceptance and has already established its place in the broad spectrum of manufacturing operations and pharmaceutical research developments. HME has already been demonstrated as a robust, novel technique to make solid dispersions in order to provide time controlled, modified, extended, and targeted drug delivery resulting in improved bioavailability as well as taste masking of bitter active pharmaceutical ingredients (APIs). This paper reviews the innumerable benefits of HME, based on a holistic perspective of the equipment, processing technologies to the materials, novel formulation design and developments, and its varied applications in oral drug delivery systems.